Ninja wars [videorecording (DVD)] = Iga ninpōchō - Saitō, Mitsumasa, 1959-; Chiba, Sonny, 1939-2021-; Sanada, Hiroyuki, 1960-; Watanabe, Noriko, 1965-; Yamada, Fūtarō, 1922-2001 (Sonny Chiba collection, 2004)
Whoever marries Princess Ukio will become the ruler of the world, so Lord Danjo makes a deal with an evil magician. With the help of a mysterious ninja, only Jotaro can stop Lord Danjo's plan and rescue the princess and her sister.